2016
DOI: 10.1002/mren.201500055
|View full text |Cite
|
Sign up to set email alerts
|

Application of Raman Spectroscopy to Characterization of Residence Time Distribution and Online Monitoring of a Pilot‐Scale Tubular Reactor for Acrylic Acid Solution Polymerization

Abstract: A pilot-scale tubular reactor containing static mixers is equipped with several Raman probes in order to perform online monitoring of radical copolymerization of acrylic acid in aqueous solution. This setup allows determination of residence time distribution while polymerization reaction occurs, using sodium nitrate as a tracer. These results prove that the use of convenient static mixers allows obtaining a nearly perfect plug-fl ow reactor in all explored conditions (reactive and nonreactive medium, between 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…Residence time distribution (RTD) of the reactor was studied in detail with nonreactive and reactive fl uids and with fl uid viscosities between 10 −3 and 1 Pa s. [ 42 ] It was demonstrated that RTD was very similar to that of a perfect plug-fl ow reactor. This assumption was made for all calculations.…”
Section: Mathematical Model Of Polymerization Reactormentioning
confidence: 98%
“…Residence time distribution (RTD) of the reactor was studied in detail with nonreactive and reactive fl uids and with fl uid viscosities between 10 −3 and 1 Pa s. [ 42 ] It was demonstrated that RTD was very similar to that of a perfect plug-fl ow reactor. This assumption was made for all calculations.…”
Section: Mathematical Model Of Polymerization Reactormentioning
confidence: 98%
“…Moreover, this type of spectroscopies, like Fourier transformed infrared (FTIR) or Raman, can be of great interest to monitor in situ structural modifications with potential applications for implementation in real-time industrial diagnosis. 16,24,25 In this article, by means of FTIR and GIWAXS, we have accomplished a detailed description of the in situ isothermal crystallization of poly(trimethylene 2,5-furandicarboxylate) (PTF) in real time. From FTIR experiments, the evolution of hydrogen bonding with crystallization time can be monitored.…”
Section: Introductionmentioning
confidence: 99%
“…Vibrational spectroscopy is a powerful tool to identify at molecular-level conformations characteristic of amorphous and crystalline phases in polymers. Moreover, this type of spectroscopies, like Fourier transformed infrared (FTIR) or Raman, can be of great interest to monitor in situ structural modifications with potential applications for implementation in real-time industrial diagnosis. ,, …”
Section: Introductionmentioning
confidence: 99%
“…However, the technical requirements for conducting the widely used Fourier-transform infrared spectroscopy (FTIR) hamper the combination with other techniques and specific complex sample environments have to be designed to be coupled for each experiment requirement. By contrast, Raman spectroscopy has been widely used in combination with multiple techniques, in particular for polymer characterization in the industrial field [ 34 , 35 ] such as monitoring of in situ polymerization by Raman spectroscopy [ 36 , 37 , 38 ] as well as rheo-Raman [ 39 ] and Raman-DSC [ 40 ], due to its simple implementation, improvement of the time resolution and experimental advantages [ 41 ]. Furthermore, Raman spectroscopy is a non-destructive technique that can be applied to different media (bulk, fibres, solution, gels and films), specifically aqueous solution without special experimental preparations, and requires small quantities of sample to be studied [ 41 , 42 ].…”
Section: Introductionmentioning
confidence: 99%